A Case Series on Arthroscopic Valvulectomy of Symptomatic Popliteal Cysts in Elderly Patients Using a Modified Gillquist Maneuveropic Valvulectomy of Symptomatic Popliteal Cysts in Elderly Patients Using a Modified Gillquist Maneuver - Braganza, Carmelo; Dominado, Julius Loren; Palpal-latoc, Leinard (Philippine Journal of Orthopaedics, 2024)
The primary objective of this study was to assess the outcomes of arthroscopic management of popliteal cysts using the modified Gillquist maneuver for visualization. The original Gillquist maneuver was originally developed to gain access to the posterior knee compartment. However, there were drawbacks, including blind arthroscope insertion, which could potentially lead to unnecessary trauma to the knee and the risk of arthroscope damage. The modified Gillquist maneuver was introduced to overcome these limitations, offering the advantage of direct visualization during arthroscope insertion into the posterior compartment through either the anterolateral or anteromedial portals. This single-institution case series focused on a cohort of five patients aged over 60 diagnosed with unilateral popliteal cysts. These individuals underwent arthroscopic valvulectomy using the modified Gillquist maneuver. The results of the procedure were highly encouraging, providing symptomatic relief for all five patients. Significant improvements were observed in clinical metrics, including the Numeric Rating Scale (NRS), Rauschning and Lindgren Criteria, Lysholm Score, and Knee Range of Motion during a follow-up period of up to 24 months. These promising outcomes highlight the potential efficacy of the modified Gillquist maneuver as a viable surgical approach for managing popliteal cysts in the elderly population.